Analysis of Cytogenetic Abnormalities in Iranian Patients with Syndromic Autism Spectrum Disorder: A Case Series - Ghasemi, Mohammad-Reza; Zargari, Peyman; Sadeghi , Hossein; Bagheri, Saman; Sadeghi , Behnia; Mirfakhraie, Reza; Ekrami, Mahdis; Mohammadi Sarvaleh , Sepideh; Hashemi-Gorji , Farzad; Razjouyan , Katayoon; Omrani , Davood; Kim , Hyung-Goo; et al. (Iranian Journal of Child Neurology, 2022)
Objective Autism spectrum disorder is a heterogeneous neuropsychiatric group of pervasive development disorder, which is mostly diagnosed through the intricate behavioral phenotype. According to strong genetic involvement, detecting the chromosome regions and the key genes linked to autism can help to elucidate its etiology. The present study aims to investigate the value of cytogenetic analysis in syndromic autism as well as to find an association between autism and chromosome abnormalities. Materials & Methods Thirty-six autism patients from 30 families, diagnosed clinically with DSM-5 criteria, were recruited. The syndromic patients who had additional clinical features involving development delay, attention deficit, hyperactivity disorder, seizure, language, and intellectual impairment were selected due to elevating the detection rate. Cytogenetics analysis was performed using GTG banding on the patients' cultured fibroblasts. Moreover, array-comparative genomic hybridization was also performed for a patient with a de novo and novel variant. Results Karyotype analysis in 36 syndromic autism patients detected chromosomal abnormalities in two (5.6%) families, including 46,XY,dup(15)(q11.1q11.2) and 46,XX,ins(7)(q11.1q21.3)dn. In the latter, array-comparative genomic hybridization detected three abnormalities on chromosome 7, including deletion and insertion on both arms; 46,XX,del(7)(q21.11q21.3),dup(7)(p11.2p14.1p12.3)dn. Conclusion We reported a novel and de novo cytogenetic abnormality on chromosome 7 in an Iranian patient diagnosed with syndromic autism. However, the detection rate in syndromic autism was low which implies that it cannot be utilized as the only diagnostic procedure.